PENGARUH PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM DI SEKTOR PERBANKAN BURSA EFEK INDONESIA DIMASA PANDEMI COVID-19 (Media Akuntansi dan Perpajakan Indonesia, 2022)
This study was conducted to determine the effect of profitability and dividend policy on stock prices during the Covid-19 pandemic separately in 2020 and 2021. This type of research uses a quantitative approach. The type of data in this study is secondary data obtained from the financial statements of the second quarter - fourth quarter 2020 and first quarter - third quarter 2021. The population in this study are companies listed on theIndonesia Stock Exchange. The sampling technique used is purposive sampling where the sample obtained in the study is 40 banking companies listed on the Indonesia Stock Exchange. This research method uses multiple linear regression analysis. This study examines separately between 2020 and 2021 to see the effect of dividend policy and ROE when the ups and downs of Covid-19 cases affect the JCI. The results show that profitability has a positive effect on stock prices, while dividend policy has no effect on stock prices during the Covid-19 pandemic. While there are two phenomena between 2020 and 2021, the high and low profitability still illustrates the company’s prospects that can attract investors so that it can affect stock prices. The results of this study can be a reference for investors to minimize investment risk before investing in stocks. Keywords: stock prices, profitability, dividend policy, Covid-19.